Taqlid and Ijtihad (American Journal of Islam and Society, 1991)
The Polemics of IjtihadFrom the second hijri century until the present day, the reality, the essence,the rules, the conditions, the premises, the means, and the scope of ijtihadhave remained a source of debate engaging some of the Islamic world's greatesttheologians, scholars of al usul, and fuqaha': This debate has also been enrichedby proponents of the view that the door of ijtihad was closed and that thefiqh left by the Four Imams obviated the need for any further ijtihad, aswell as by those who claimed that this door was still open and that the existingfiqh was not sufficient to guide the contemporary Muslim world.In our own times, attention is now focused on the suitability of the Shari'ahas an order and a way of life. This new topic of debate, before unknownamong Muslims, emerged after the crushmg defeats experienced by the Muslimummah after the First World War, such as the dismantling of the khihfahand the creation of artificial states ruled from Europe. Many Muslims blamedIslam and its institutions for their defeat, and soon began to emulate theirconquerors. Others, however, had a quite different view: the Muslim ummahexperienced these disasters because it had become alienated from the eternaltruths of Islam. Thus, what was required was a return to the true Islam andnot its wholesale rejection in favor of alien institutions and ideologies. Onefundamental part of this return would have to be the use of ijtihad, for howelse could Muslims incorporate Islamic principles into situations with whichthey had never had to deal?Muslims who hold the latter view are aware of the fact that they mustmeet their opponents in the realm of ideas, for it is here that the future courseof the ummah will be decided. To be successful, much energy must beexpended in scholarship and conceptual thinking, in seeking to understandhumanity's place in the divine scheme of existence and what is expected ofit, and how this knowledge might be applied by Muslims as they struggle ...